Budd-Chiari Syndrome: What is the Cause? - Sara Mustafa,Aarifa Batool, Muhammad Khurram, Tanveer Hussain, Arshad Rabbani, Imran Arshad, Muhammad Umar Daraz, Murtaza Asghar, Sara Mustafa,Aarifa Batool, Muhammad Khurram, Tanveer Hussain, Arshad Rabbani, Imran Arshad, Muhammad Umar Daraz, Murtaza Asghar (Journal of Rawalpindi Medical College, 2018)
Budd-Chiari syndrome (BCS) is a rare condition. It results from occlusion of hepatic venous outflow. Abdominal pain, ascites, and liver enlargement are classic triad symptoms in BCS. Myeloproliferative disorders, thrombophilias, malignancy, and infections are common etiological factors for BCS.1It can be due to thrombotic or nonthrombotic obstruction of hepatic venous outflow. It was first described by Budd in 1845 and subsequently by Chiari in 1899.2,3 Site of hepatic outflow obstruction in BCS is variable. It is frequently noted at level of inferior vena cava (IVC) and hepatic veins. Untreated patients with BCS have poor prognosis. Death occurs due to progressive liver failure in three months to three years after the diagnosis is made.4 With shunt procedures and liver transplantation, 5 year survival is up to 87%.5,6,7 Here we describe a patient with BCS, who was diagnosed at our Medical Unit. Etiology of BCS could not be made. Patient was managed conservatively as he deferred interventional radiological procedure Diagnosis of BCS was made on CT scan and subsequent Doppler ultrasonography